Differences in neurotransmitter systems of ventrolateral periaqueductal gray between the micturition reflex and nociceptive regulation: An in vivo microdialysis study. (8th April 2016) - Kitta, Takeya; Mitsui, Takahiko; Kanno, Yukiko; Chiba, Hiroki; Moriya, Kimihiko; Yoshioka, Mitsuhiro; Shinohara, Nobuo
Abstract : Objectives: To elucidate the possible involvement of glutamate and serotonin (5‐hydroxytryptamine) neurons in the ventrolateral midbrain periaqueductal gray during noxious stimulation. Methods: The study was carried out by evoking a noxious stimulation by acetic acid in an animal model of cystitis. Changes in glutamate and 5‐hydroxytryptamine in the periaqueductal gray during the micturition reflex and acetic acid‐induced cystitis were determined using in vivo microdialysis combined with cystometry in rats. Results: Extracellular glutamate levels slightly, but significantly, increased during the micturition reflex induced by saline infusion into the bladder. Intravesical infusion of acetic acid facilitated the micturition reflex characterized by increases in voiding pressure and decreases in the intercontraction interval. Glutamate levels were markedly increased by acetic acid, and this enhancement was sustained for at least 3 h. 5‐Hydroxytryptamine levels, which were not altered during the micturition reflex, were increased after intravesical infusion of acetic acid. Conclusion: The results suggest that periaqueductal gray glutamate and 5‐hydroxytryptamine neurons differentially participate in the modulation of both nociception and the micturition reflex. Furthermore, periaqueductal gray 5‐hydroxytryptamine levels appear to reflect the nociceptive stimuli.